The effects of lung recruitment on the phase III slope of volumetric capnography in morbidly obese patients - Bohm, Stephan H. (2008)
In this study, we analyzed the effect of the alveolar recruitment strategy (ARS) and positive end-expiratory pressure (PEEP) titration on Phase III slope (S III) of volumetric capnography (VC) in morbidly obese patients. METHODS: Eleven anesthetized morbidly obese patients were studied. Lungs were ventilated with tidal volumes of 10 mL · kg−1, respiratory rates of 12–14 bpm, inspiration:expiration ratio of 1:2, and Fio2 of 0.4. ARS was performed by increasing PEEP in steps of five from 0 end-expiratory pressure to 15 cm H2O. During lung recruitment, plateau pressure was limited to 50 cm H2O, whereas tidal volume was increased to the ventilator’s maximum value of 1400 mL, and PEEP was increased to 20 cm H2O for 2 min. Thereafter, PEEP was reduced in steps of 5 cm H2O, from 15 to 0. VC, arterial blood gases, and lung mechanics data were determined for each PEEP step. RESULTS: S III decreased from 0.014 ± 0.006 to 0.005 ± 0.005 mm Hg/mL when 0 end-expiratory pressure was compared against 15 cm H2O of PEEP after ARS (15ARS, P < 0.05). This decrement in S III was accompanied by increases in Pao2 (27%, P < 0.002) and compliance (32%, P < 0.001), whereas Paco2 decreased by 8% (P < 0.038) when comparing values before and after ARS. A good prediction of the lung recruitment effect by S III was derived from the receiver operating characteristic curve analysis (area under the curve of 0.81, sensitivity of 0.75, and specificity of 0.74; P < 0.001). CONCLUSION: The S III in VC was useful to detect the optimal level of PEEP after lung recruitment in anesthetized morbidly obese patients.